2001
DOI: 10.1063/1.1424479
|View full text |Cite
|
Sign up to set email alerts
|

Border traps in 6H-SiC metal–oxide–semiconductor capacitors investigated by the thermally-stimulated current technique

Abstract: We demonstrate the usefulness of the thermally-stimulated current (TSC) technique for investigating shallow interface state defects in silicon carbide metal–oxide–semiconductor (MOS) structures. For dry oxides, low-temperature TSC measurements reveal a high density of near-interfacial oxide traps (border traps) close to the band edges of 6H–SiC. Furthermore we find that annealing the SiC/SiO2 interface in pyrogenic steam at 950 °C (reoxidation) essentially reduces the density of deep interface states, while it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…However, to discuss accurately the effects on l FE , the total D IT including the interface states that trap electrons at high gate voltage (or electric field) is necessary. Other techniques such as Halleffect measurements [23][24][25] or thermally-stimulated-current measurements 26,27 are necessary to evaluate the interface states at high gate voltage (or electric field). Okamoto et al showed the effect of trapped electrons that increase with oxide electric field on the field-effect mobility.…”
mentioning
confidence: 99%
“…However, to discuss accurately the effects on l FE , the total D IT including the interface states that trap electrons at high gate voltage (or electric field) is necessary. Other techniques such as Halleffect measurements [23][24][25] or thermally-stimulated-current measurements 26,27 are necessary to evaluate the interface states at high gate voltage (or electric field). Okamoto et al showed the effect of trapped electrons that increase with oxide electric field on the field-effect mobility.…”
mentioning
confidence: 99%
“…In principle, detection of defects can be done either indirectly, through their effect on the physical/electrical properties of the semiconductor, or directly by 3D structural imaging. The physical/electrical activity of the defects can be detected and characterized by techniques such as ESR, 111–115 NMR, 116–118 deep level transient spectroscopy, 119–121 and thermally stimulated current 122,123 . For large enough samples, these types of measurements can be used to detect even low densities of electrically active defects (introducing levels in the forbidden energy gap).…”
Section: Possible Applicationsmentioning
confidence: 99%
“…Lysenko et al 11 and Ó lafsson et al 12 observed for the case of 6H-SiC a dependence of the 40-K peak on the accumulation field. In our work, this dependence was observed for the 80-K peak in 4H-SiC (e.g., Fig.…”
Section: Tsc Spectra Of Mosfet Source/body N + -P Junctionmentioning
confidence: 99%
“…10 Previous reports of TSC measurements on SiC have focused on metal-oxide-semiconductor (MOS) capacitors fabricated on n-and p-type 4H-and 6H-epitaxial layers. [11][12][13][14] Studies of p-type 6H-SiC MOS capacitors by Lysenko et al 11 and Ó lafsson et al 12 showed two main peaks in the TSC spectra, located at approximately 50 K and 70 K. The origin of the former peak was attributed to interface states, whereas the latter was concluded to be due to Al acceptors (E A = 160 meV to 230 meV). [15][16][17] On n-type 4H-SiC, Rudenko et al observed TSC peaks near 40 K, 90 K, and 150 K. 13,14 The 40-K peak was attributed to N donor ionization, and the other two peaks were due to the presence of interface states near the conduction band.…”
Section: Introductionmentioning
confidence: 99%